Predicting institutionalization after Subacute Stroke Rehabilitation using the 12-Item World Health Organization Disability Assessment Schedule - Tarvonen-Schröder Sinikka; Koivisto Mari (FOUNDATION REHABILITATION INFORMATION, 2025)
Objective: To evaluate the utility of the 12-item World Health Organization Disability Assessment Schedule (WHODAS-12) in predicting institutionali-zation after subacute stroke rehabilitation.
Design: Prospective observational study.
Methods: On a specialized rehabilitation ward, discharge WHODAS-12 scores of 156 consecu-tive patients (24-h National Institutes of Health Stroke Scale (NIHSS) & GE; 15) and assessment from their proxies were compared, and receiver ope-rating characteristic curves for predicting insti-tutionalization were generated. Clinician-rated assessments of functioning were applied for com-parison.
Results: Thirty-three percent of the patients were unfit to respond, due to the consequences of major stroke. However, both patient and proxy WHO-DAS-12 sum scores differentiated the community (n = 70) and institution (n= 86) groups (p= 0.02 and p < 0.0001, respectively), the discriminative accuracy (area under the curve; AUC) being 0.63 and 0.79, respectively. In proxy assessments, the institutionalized patients were significantly more impaired in all item comparisons except for emo-tions and concentrating. Ability to participate dif-ferentiated the groups as accurately as activities (AUC 0.75 vs 0.78, respectively). The corresponding discriminative accuracy of the clinician-rated World Health Organization (WHO) minimal generic data -set sum score and modified Rankin Scale were 0.74 and 0.79 (p< 0.0001), respectively.
Conclusion: Despite its brevity and subjectivity, the WHODAS-12 from proxies has shown high accuracy in predicting institutionalization after subacute rehabilitation of individuals with major stroke, the impact of participation being as relevant as that of activities.